Role of Bacillus thuringiensis in development of transgenic plants - Ramyashree, C S; Carol, C Morris; Kruthika, P; Manikantan, Pappuswamy; Aditi, Chaudhary; Arun, Meyyazhagan; Vijaya Anand, Arumugam; Balamuralikrishnan, Balasubramanian (Plant Science Today, 2023)
One of the most significant advancements in plant biotechnology has been the production of genetically engineered plants. Due to the effects of pests damaging the majority of crops, the development of pest immunity was necessary for crop preservation. Plants that have had their gene makeup altered in-utero, such as Bacillus thuringiensis, which has insecticidal properties and helps protect crops from pests, are referred to as "genetically modified plants." Cry proteins, which are poisonous proteins that exist in the state of crystals, are the major genes responsible for the development of transgenic plants. Based on the effect of different pest species, cry proteins are divided into many categories. Since they are extremely specific by nature and only affect the target proteins, they are considered environmentally beneficial pesticides since they have no impact on the physiologically significant soil bacteria or other bacterial flora. These cry proteins stay as dormant crystals, but when a pest consumes plants, the inactive form of the crystals becomes active in the alkaline stomach pH of the microorganism, aiding in the rupture of the gut epithelium and ultimately causing the microorganism to die. These days, transgenic plants have been created, including BT corn, BT rice, sugarcane, brinjal, potato, tomato, and many more, it was also discovered that using these transgenic plants increased crop productivity. Transgenic plants can prevent several ecological issues associated with traditional pesticides, including the emergence of resistance, their toxicity to non-target living things, and the buildup of toxic waste in the environment.